2015
DOI: 10.1016/j.jastp.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of tropical stratospheric ozone to rotational UV variations estimated from UARS and Aura MLS observations during the declining phases of solar cycles 22 and 23

Abstract: of tropical stratospheric ozone to rotational UV variations estimated from UARS and Aura MLS observations during the declining phases of solar cycles 22 and 23. Journal of Atmospheric and Solar-Terrestrial Physics, Elsevier, 2015, 130-131, pp.96-111. <10.1016/j.jastp.2015 AbstractThe correlation between tropical stratospheric ozone and UV radiation on solar rotational time scales is investigated using daily satellite ozone observations and reconstructed solar spectra.We consider two 3-year periods falling wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Furthermore, the overall variation of the time lag with altitude shown in Fig. 6 is similar to that found in previous studies (Hood, 1986;Brasseur et al, 1987;Brasseur, 1993;Hood and Zhou, 1998) with a negative lag above 3-4 hPa (ozone "leading" the solar flux) and a positive lag below (ozone lagging the solar flux). As mentioned in the Introduction, the negative lag in the upper stratosphere results of the influence of the temperature feedback on the ozone response through the temperature dependent chemical reactions.…”
Section: Observed and Modeled Ozone Response To The Rotational Cyclesupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the overall variation of the time lag with altitude shown in Fig. 6 is similar to that found in previous studies (Hood, 1986;Brasseur et al, 1987;Brasseur, 1993;Hood and Zhou, 1998) with a negative lag above 3-4 hPa (ozone "leading" the solar flux) and a positive lag below (ozone lagging the solar flux). As mentioned in the Introduction, the negative lag in the upper stratosphere results of the influence of the temperature feedback on the ozone response through the temperature dependent chemical reactions.…”
Section: Observed and Modeled Ozone Response To The Rotational Cyclesupporting
confidence: 88%
“…However, they noticed that including the solar induced temperature changes alone was not sufficient to adequately reproduce the observed magnitude and phase lag of the ozone response and suggested that atmospheric dynamical variability -which is not simulated in 1-D models -may also have a sizeable influence (Hood, 1986;Brasseur et al, 1987). The latter issue has later been addressed with two-dimensional models which revealed better agreement with observations (Brasseur, 1993;Fleming et al, 1995;Chen et al, 1997). Fleming et al (1995) further stressed the increasing importance with height of the solar-modulated HO x chemistry on the ozone response above 45 km.…”
Section: Introductionmentioning
confidence: 89%
“…A statistically significant solar signature is found in tropics in both CCMs and observations but the solar signature is generally underestimated in CCMs. Note that the solar component results are found to be strongly dependent on the length of the data series (Bossay et al, 2015). For both observations and CCMs, the amount of variance explained by the aerosol forcing is very variable and strongly depends on the period covered by the time series, whether it is background (nonvolcanic) or volcanically active periods.…”
Section: Discussionmentioning
confidence: 93%
“…It is likely that only MLR analysis on time series of at least several decades can provide robust and reliable estimates of ozone column sensitivities to solar variations for monthly mean data, especially at high latitudes (see Figure 14). If daily data have been considered, a solar signal could have been extracted from much shorter time series because of an important periodicity in the solar activity, the 27-day solar rotational cycle (Rozanov et al, 2006;Fioletov, 2009;Bossay et al, 2015).…”
Section: Absolute Contributions Of External Forcings To Interannual Vmentioning
confidence: 99%
“…It is already well established that a substantial component of stratospheric ozone variability originates from short-term and long-term quasi-periodic fluctuations in solar activity, notably the 11-year solar magnetic activity cycle (also called the Schwabe cycle) and the 27-day solar rotational cycle (also called the Carrington cycle). Numerous observational (Bossay et al, 2015;Chandra & McPeters, 1994;Dikty et al, 2010;Fioletov, 2009;Hood, 1986;Hood & Zhou, 1998;Ruzmaikin et al, 2007;Zhou et al, 1997;Zhou et al, 2000) and modeling (Austin et al, 2007;Brasseur, 1993;Gruzdev et al, 2009;Merkel et al, 2011;Rozanov et al, 2006;Sukhodolov et al, 2017;Thiéblemont et al, 2017;Williams et al, 2001) studies have demonstrated the influence of the 27-day solar rotational cycle on stratospheric ozone. The main process responsible for the stratospheric ozone response to solar variability is the solar UV-driven photolysis of molecular oxygen (O 2 ) that is the source of O 3 in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%